Duiliu Zamfirescu - Eugen Simion (Revista de Istorie și Teorie Literară)
The second part of Academician Eugen Simion’s article on Duiliu Zamfirescu discusses Tănase Scatiu, an excellent realist work which continues the story from Viaţa la ţară, and whose main character represents a new social class. În război uses historical documents to give authenticity to the fiction in a way that shows the author’s admiration for war. The novel also closely follows the intimate life of its characters, however it does not do it in depth, and this becomes inauthentic in the next books of the series. But this exercise is beneficial, as a new type of character (the independent woman) is cleverly introduced, while another is almost being psychoanalysed. At the same time, classic themes such as love, beauty, jealousy are symbolically at war, all these elements making În război a notable early modernist work. The following novels Îndreptări and Anna (Ceea ce nu se uită) continue analysing feminine psychology without reaching the previous esthetical quality. The latter, although it introduces new hypotheses in Romanian literature, lacks subtlety or consistency, and its characters are both moralizing and morally ambiguous. Lydda departs from Zamfirescu’s view of women as irrational as he attempts to create an ode to love and to describe the sublime woman. An interesting philosophical and moralizing experiment, the novel evolves between a disappointed father and a hopeful son. Familiar themes – marriage, love, femininity – return, but this time they are illustrated using different instruments.